2011
DOI: 10.2118/148630-pa
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Of Methane, Nitrogen, and Carbon Dioxide in Bitumen and Water for SAGD Modelling

Abstract: Summary Gases such as carbon dioxide, nitrogen, and methane that can be present in a steam-assisted gravity-drainage (SAGD) steam chamber (but do not condense into the liquid phase to any large degree at reservoir conditions) are referred to as noncondensable gases (NCGs). The coinjection of NCGs with steam during SAGD results in changes in production rate, total oil production, and the amount of steam required to mobilize the bitumen in place. To investigate the impact of NCGs on SAGD performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Under the same conditions, the solubility of nitrogen in water is less than that of methane, which results in the liquid drainage rate of the nitrogen foam being less than that of the methane foam, so the nitrogen foam has better stability. 29 Finally, surfactant S-B was selected. The amphoteric surfactant was compatible with the other types of surfactants, especially those capable of accepting a proton, and it may also exhibit synergy with the anionic surfactant through electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under the same conditions, the solubility of nitrogen in water is less than that of methane, which results in the liquid drainage rate of the nitrogen foam being less than that of the methane foam, so the nitrogen foam has better stability. 29 Finally, surfactant S-B was selected. The amphoteric surfactant was compatible with the other types of surfactants, especially those capable of accepting a proton, and it may also exhibit synergy with the anionic surfactant through electrostatic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of whether NPs are added or not, the pressure increase rate and the amplitude of the methane foam are weaker than those of the nitrogen foam, which is related to the properties of methane and nitrogen. 29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous numerical and experimental studies investigating various aspects of solvent-aided recovery processes. Al-Murayri et al considered the impact of the noncondensable gases as possible solvents in a hybrid process with the conventional SAGD. Their simulation results revealed that while co-injection of a noncondensable gas such as methane reduces the heat loss to the overburden, it negatively impacts the oil recovery by affecting the steam condensation.…”
Section: Introductionmentioning
confidence: 99%
“…Core flooding experiments have also been conducted to study the ability of immiscible CO 2 to increase oil recovery [18]. Immiscible CO 2 injection has also been coupled with other injection fluids such as water, and steam in hopes of increasing oil recovery [19][20][21]. Due to the abundance of methods by which oil swelling can be measured, and the many ways by which immiscible CO 2 injection can be applied, it is important to provide a guideline to these methods and their advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%